Learning configural spatial knowledge from navigating in unstructured and unfamiliar virtual environments. (September 2018) - May, Robert B.; Colle, Herbert A.
Lynch's (1960) description of the importance of districts for spatial memory was used as a basis for looking at the contributions of semantic meaning and physical structure to learning configural spatial knowledge about an unfamiliar virtual environment. According to Lynch, meaningful grouping, not just geometric structure should facilitate spatial learning, perhaps also assisted by structure. In a virtual environment consisting of four rooms/quadrants, both the presence or absence of walls and the semantic organization of the landmark objects (grouped versus distributed category members) were factorially combined. Both object locations and navigation paths were randomly determined. Angular error was reduced by the presence of walls and by the grouping of category members in rooms/quadrants, particularly when walls were present. Performance was better than chance even when object categories were distributed evenly throughout the environment and walls were not present. The theoretical and practical implications of these results were described.